Importance of the super formula in the teaching of fractal geometry. - García Pinilla, Camilo Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The objective of the work seeks to guide the basic concepts of Euclidean Geometry that students of the Colegio de Educación Formal Flexible San Mateo have, in this sense to be able to analyze different representations of nature through the super Lame Gielis formula, as a strategy for learning fractal geometry, making use of the Geogebra virtual tool. Its methodological development is based on a qualitative paradigm (Sandoval Casilimas, 2002) which focuses its development on the understanding and analysis of the different behaviors that individuals study from the following phases Methodological: Observation phase, Creation phase, Application phase and Sustaining phase